2022
DOI: 10.3390/ijerph191610331
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance Tests in Adult Neck Pain Patients with and without Clinical Myelopathic Signs: A Matched Case-Control Study

Abstract: Patients with neck pain may experience cervical myelopathy, this may be detected by clinical myelopathic signs, although they did not have any symptom of myelopathy, except having neck pain. Decreasing physical performance is one symptom of cervical myelopathy that can lead to reduced quality of life in the elderly, however, in adult neck pain with clinical myelopathic signs have not been evaluated. Therefore, this research aimed to compare physical performance in two groups of adult patients with neck pain: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 48 publications
(73 reference statements)
2
5
1
Order By: Relevance
“…The prevalence of finger escape signs was 28.27%, which conflicts with the study of Hnin Lwin et al [26], who reported the prevalence at 10% [26]. This difference may be because the current study included younger participants.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…The prevalence of finger escape signs was 28.27%, which conflicts with the study of Hnin Lwin et al [26], who reported the prevalence at 10% [26]. This difference may be because the current study included younger participants.…”
Section: Discussioncontrasting
confidence: 80%
“…Participants were eligible for inclusion if they (i) were university students, (ii) had reported neck pain for more than three months [29], (iii) had reported daily smartphone use of at least two hours per day for more than six months [30], and (iv) had a pain score between 3-7 on the visual analog scale (VAS) [31]. Participants were excluded if they (i) had a positive jaw jerk; (ii) had a positive Spurling test; (iii) had a history of previous cervical spine surgery; (iv) were concurrently suffering from other locomotor disorders; (v) had a history of brain trauma; (vi) had comorbid neurological diseases, such as cerebral infarction or neuropathy; (vii) had consumed any sedative drugs or alcohol within the past 48 h; or (viii) were pregnant [26].…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations